Chronic suppurative otitis media – comorbidities, management and return to sports activities - Olędzka, Joanna; Kopacz, Wojciech; Kruczyk, Barbara; Piętak, Mateusz; Stradczuk, Monika; Czach, Zuzanna; Bachurska, Dominika; Rękas, Barbara; Mazurek, Wojciech (Quality in Sport, 2024)
Chronic suppurative otitis media (CSOM) remains a significant clinical challenge in otorhinolaryngology, characterized by prolonged inflammation of the middle ear and mastoid space, accompanied by a perforated tympanic membrane and persistent discharge for a minimum of two weeks. Despite its often viral origin, bacterial colonization is common, with frequent involvement of pathogens such as Pseudomonas aeruginosa, Staphylococcus aureus and Klebsiella pneumoniae. CSOM affects over 300 million individuals worldwide, primarily in low socio-economic communities, and is prevalent among children due to acute otitis media (AOM) or congenital disorders. In adults, it is often associated with conditions such as cholesteatoma or polyps. Approximately 60% of CSOM patients suffer from conductive hearing loss, which can impair speech development in children. This review discusses the etiological factors, associated complications, and treatment options for CSOM, emphasizing the importance of accurate diagnosis and comprehensive management, including potential surgical interventions. The persistent and recurrent nature of AOM, anatomical abnormalities, presence of polyps, primary ciliary dyskinesia, and cholesteatoma are highlighted as significant contributors to the development and perpetuation of CSOM. To complete discussion, there is a brief review of management in recovery after elaborated conditions with special regards to returning to physical activities.